Secondary forest: a working definition and typology - Chokkalingam, U.; Jong, W. de (2001)
With past and continued destruction of primary forest worldwide, secondary forest constitute a large and growing component of forest cover and have been found to be very important for a wide range of goods and services. Despite its widespread usage, there is considerable ambiguity with regard to the meaning of the term 'secondary forest' and the different forest types it encompasses. This paper reviews existing definitions, or perceptions, of secondary forests and examines the three main points of contention: nature (human or natural) of disturbance, intensity of disturbance, and nature of vegetation development matters in its definition. It then arrives at a broad working definition for secondary forests, and develops a secondary forest typology based on the underlying disturbances or land use practices that create conditions for the appearance of secondary forest. Both the definition and typology are based on clear and objective criteria and are generalizable across regions, which should make them widely applicable.